Emha Ainun Nadjib Qur'anic Tadabbur as a Manifestation of Qur’anic Epistemology in Reading Reality - Wildan Fahdika Ahmad (Ar-Rasikhin : Jurnal Ilmu Al-Qur'an dan Tafsir, 2026)
This study examines Emha Ainun Nadjib's interpretation of the Qur'an as a form of epistemological praxis of the Qur'an in understanding social and cultural realities. This study uses qualitative research and library study methods, as well as an epistemological approach, focusing on Nadjib's works that represent his interpretation of the Qur'an. The results show that Nadjib's interpretation of the Qur'an emphasizes contextualization, dialogical interaction between text and reality, and the epistemological function of the Qur'an. This perspective offers an alternative to conventional interpretation or exegesis by emphasizing practical epistemology rather than purely theoretical hermeneutics. The concrete contribution of this research demonstrates that the epistemology of the Qur'an can be adopted and practiced by everyone in acquiring knowledge.